Assessing the effectiveness of mangrove rehabilitation using above-ground biomass and structural diversity - Asamaporn Sitthi; Uday Pimple; Camille Piponiot; Valery Gond (Scientific Reports, 2025)
Abstract Understanding the carbon sequestration potential of undisturbed and rehabilitated mangrove ecosystems is crucial for mitigating the effects of climate change. In this study, the above-ground biomass (AGB) and structural complexity of natural, rehabilitated and regenerated mangrove forest stands were investigated. Using 32 years of Landsat time series-based normalized difference infrared index data and transect field inventory methods, we examined species and structural diversity as well as AGB distribution across 24 plots spanning a gradient from sea to land. A common allometric model and linear regression analysis were used to evaluate the influence of species diversity, structural complexity, and tree density on AGB. The results revealed that natural mangrove stands exhibited higher AGB, structural complexity, and species diversity than the rehabilitated and regenerated stands. The Shannon diversity index had a negligible effect on AGB, whereas structural complexity significantly influenced AGB in natural stands. This may be attributed to the predominance of rehabilitated monoculture and less diverse scrub mangroves in natural stands. Total AGB ranged from 45.05 to 536.48 tons/ha in natural stands and from 61.57 to 98.99 tons/ha in rehabilitated stands. Our findings illustrate the challenges (e.g., high-density plantation practices, lack of species diversity, and unsuitable site conditions for planted species) associated with current rehabilitation efforts and provide insights for optimizing future rehabilitation strategies.